Copper-based composite membrane and method for manufacturing the same
The copper-based composite film addresses the issue of high resistivity in existing films by utilizing a high content of flake-like copper powder and low-temperature heat treatment to achieve enhanced electrical and thermal conductivity, suitable for various conductive applications.
Patent Information
- Application Number
- JP2023146064
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-08
- Publication Date
- 2025-03-21
AI Technical Summary
Existing copper-based composite films suffer from insufficient continuity of flake-like copper powders, leading to high resistivity and unsuitability for applications requiring electrical conductivity.
A copper-based composite film with a high content of flake-like copper powder (70% by weight or more), high planar density, and specific crystal lattice surface ratios, achieved by low-temperature heat treatment, ensuring adjacent copper powders come into contact for enhanced conductivity.
The resulting copper-based composite film exhibits excellent electrical and thermal conductivity, making it suitable for applications such as electrodes, circuits, and heat dissipation sheets, while being produced through a simple and cost-effective low-temperature process.
Smart Images

Figure 2025039173000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a copper-based composite film, specifically, a copper-based composite film having high conductivity because the flaky copper powder has a high planar density and is laminated in an arrangement that allows the flaky copper powder particles to easily come into contact with each other, and further, the copper-based composite film can be produced by low-temperature heat treatment. [Background technology]
[0002] In general, copper, which has excellent electrical and thermal conductivity (hereinafter sometimes referred to as "conductivity"), is used as a material for forming electronic components such as electrodes and circuits, and thermally conductive layers such as electromagnetic wave shielding layers and heat dissipation sheets.
[0003] The copper-based composite film can be produced by kneading copper powder with a vehicle prepared by kneading a polymer resin and an organic solvent to form a paste, applying the paste to an insulating substrate by printing or the like to form a coating film, and solidifying the paste by heat treatment (hereinafter sometimes referred to as "solidification").
[0004] It is believed that the volume of the copper-based composite film shrinks during the heat treatment process, causing adjacent copper powder particles to come into contact with each other and exhibit conductivity.
[0005] An object of the present invention is to produce a copper-based composite film that exhibits high electrical and thermal conductivity by increasing the planar density of copper powder, arranging adjacent copper powder particles so that they are easily in contact with each other, and then heat-treating the film at a low temperature. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] Patent Publication No. 2014-222619 Summary of the Invention [Problem to be solved by the invention]
[0007] Patent Document 1 describes a conductive film containing at least flaky copper powder and a resin, characterized in that the metal area ratio [(B / A)×100], which is the ratio of the area B of the flaky copper powder to the total effective area A of a cross-sectional photograph image of the conductive film taken by a scanning electron microscope, is 60% or more.
[0008] However, the conductive film described in Patent Document 1 has a problem in that the continuity of the flaky copper powder contained in the conductive film is generally insufficient, making it impossible to reduce the resistivity to near the inherent resistivity of copper, and thus making the conductive film unsuitable for applications requiring electrical conductivity.
[0009] The inventors set out to solve the above-mentioned problems as a technical objective, and as a result of repeated trial production and evaluation, they discovered that if a copper-based composite film has a flaky copper powder content of 70% by weight or more and 95% by weight or less, a relative density to the theoretical density of 50% or more, and an integrated intensity ratio of the copper crystal lattice plane (220) to the copper crystal lattice plane (111) measured by X-ray diffraction of 1 or more, then the flaky copper powder has a high planar density and is layered in an arrangement in which adjacent flaky copper powder particles are in contact with each other, then the copper-based composite film has high conductivity and can be produced by low-temperature heat treatment, and thus the above-mentioned technical objective has been achieved. [Means for solving the problem]
[0010] The above technical problems can be solved by the present invention as follows.
[0011] The present invention relates to a copper-based composite film, which has a flaky copper powder content of 70% by weight or more and 95% by weight or less, a relative density of 50% or more with respect to the theoretical density, and an integrated intensity ratio of copper crystal lattice plane (220) to copper crystal lattice plane (111) by X-ray diffraction of 1 or more.
[0012] The present invention also relates to the copper-based composite film, wherein the resistivity is 50 μΩ·cm or less.
[0013] The present invention also relates to a flaky copper powder for a copper-based composite film according to claim 1 or 2, in which the crystallite size of the copper crystal lattice plane (111) determined by X-ray diffraction is 35 nm or less, the "50% cumulative particle size" / "particle size calculated from the BET specific surface area of the flaky copper powder" is 10 or more, the frequency of particle sizes of 51.19 μm or more is 5% or less, and the copper content is 93% by weight or more.
[0014] The present invention also provides a method for producing the copper-based composite film, which comprises applying a paste containing flaky copper powder, a polymer resin and a solvent, followed by heat treatment.
[0015] The present invention also relates to the method for producing a copper-based composite membrane, wherein the polymer resin is polyvinyl butyral and / or methyl methacrylate polymer, and the solvent is butyl carbitol acetate and / or butyl carbitol.
[0016] The present invention also relates to the method for producing a copper-based composite film, wherein the heat treatment is performed in a nitrogen gas atmosphere or an argon gas atmosphere at a temperature range of 200° C. or higher and 300° C. or lower.
[0017] The present invention also relates to the method for producing a copper-based composite film, wherein the heat treatment is a heat treatment (heat treatment 1) in an air atmosphere at a temperature range of 150°C or more and 200°C or less, and a heat treatment (heat treatment 2) in an atmosphere of a mixed gas of nitrogen gas and hydrogen gas or an atmosphere of a mixed gas of argon gas and hydrogen gas at a temperature range of 200°C or more and 300°C or less, which is repeated at least once. Effect of the Invention
[0018] The present invention provides a copper-based composite film in which flaky copper powder particles are autonomously dispersed and layered, the flaky copper powder particles have a high planar density, and adjacent flaky copper powder particles come into contact with each other by heat treatment at a low temperature, resulting in excellent electrical and thermal conductivity.
[0019] Therefore, the copper-based composite film of the present invention can be suitably used for electrical conductive parts such as electrodes, circuits, and electromagnetic shielding layers, and for thermal conductive materials such as thermal conductive layers for heat dissipation sheets and the like.
[0020] The copper-based composite film of the present invention can be produced by a simple method in which a paste containing flaky copper powder, a polymer resin, and a solvent is applied to form a coating film, which is then heat-treated at a low temperature.
[0021] Furthermore, if the polymer resin is polyvinyl butyral and / or methyl methacrylate polymer, and the solvent is butyl carbitol acetate and / or butyl carbitol, a copper-based composite film with even better conductivity can be produced.
[0022] Moreover, the present invention can be produced by a low-temperature heat treatment at 200° C. to 300° C. in a nitrogen gas atmosphere or an argon gas atmosphere.
[0023] Alternatively, the semiconductor device can be produced by repeating a heat treatment (heat treatment 1) in an air atmosphere at a temperature range of 150°C to 200°C and a heat treatment (heat treatment 2) in an atmosphere of a mixed gas of nitrogen gas and hydrogen gas or an atmosphere of a mixed gas of argon gas and hydrogen gas at a temperature range of 200°C to 300°C one or more times.
[0024] Furthermore, by repeating the heat treatment 1 and the heat treatment 2 two or more times, a copper-based composite film with even better conductivity can be produced. [Brief description of the drawings]
[0025] [Figure 1] FIG. 2 is a graph showing the relationship between the content of flaky copper powder contained in a copper-based composite film and resistivity. [Diagram 2] FIG. 1 shows X-ray diffraction profiles of copper-based composite films in which the integrated intensity ratio of the (220) crystal lattice plane of copper to the (111) crystal lattice plane is 1 or more (a) and less than 1 (b). [Diagram 3]Scanning electron microscope images ((a) 5,000x and (b) 2,000x) showing the cross-sectional structure of copper-based composite films where the integrated intensity ratio of the (220) to the (111) crystal lattice plane of copper measured by X-ray diffraction is greater than 1 (a) and less than 1 (b). [Figure 4] FIG. 1 is a diagram showing X-ray diffraction profiles of copper-based composite films depending on the shape of copper powder. [Diagram 5] FIG. 2 is a graph showing the weight change of a polymer resin by thermogravimetry. [Figure 6] FIG. 1 shows the progression of X-ray diffraction patterns for an undried coating film (a), a coating film dried at 150°C in air (b), and a copper-based composite film after heat treatment at 200°C in nitrogen gas (c). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0026] In this specification, the 50% cumulative particle size is sometimes referred to as the "50% diameter," and the particle size calculated from the BET specific surface area of the flaky copper powder is sometimes referred to as the "BET diameter." The spherical volume equivalent particle diameter is referred to as the "particle diameter".
[0027] The copper-based composite film of the present invention has a relative density of 50% or more with respect to the theoretical density.
[0028] If it is less than 50%, the density of the coating film and the continuity of the flaky copper powder are partially impaired, and the conductivity may decrease.
[0029] The density of the copper-based composite film varies depending on the ratio of copper to polymer resin. If the density of the composite film at each ratio is taken as the theoretical density of the copper-based composite film at each ratio, the theoretical density can be calculated by the following (Equation 1).
[0030]
number
[0031] The density of the copper-based composite film can be calculated by measuring the weight and volume of the copper-based composite film, and the relative density of the copper-based composite film can be calculated by the following (Equation 2).
[0032] (Formula 2) Relative density of copper-based composite film (%) = 100 x (density of copper-based composite film / theoretical density of copper-based composite film)
[0033] The copper-based composite film of the present invention has an integrated intensity ratio of copper crystal lattice plane (220) to copper crystal lattice plane (111) (hereinafter sometimes referred to as "integral intensity ratio") of 1 or more, as determined by X-ray diffraction.
[0034] The profile of a copper-based composite film with an integrated intensity ratio of 1 or more is shown in Figure 2(a), and the profile of a copper-based composite film with an integrated intensity ratio of less than 1 is shown in Figure 2(b).
[0035] FIG. 3 shows scanning electron microscope images illustrating the cross-sectional structure of a copper-based composite film (a) with an integrated intensity ratio of 1 or more and a copper-based composite film (b) with an integrated intensity ratio of less than 1.
[0036] When the integrated intensity ratio is less than 1, the X-ray diffraction profile shows an isotropic crystal structure (Fig. 2(b)), and the flake-shaped copper powder contained in the copper-based composite film autonomously disperses and arranges in uniform layers during the lamination process, becoming disordered without being laminated (Fig. 3(b)).
[0037] If the flake-shaped copper powder contained in the copper-based composite film does not disperse autonomously and arrange itself in uniform layers during the lamination process, but becomes disordered, the volume of the areas containing only copper-free polymer resin and the volume of the spaces containing neither copper nor polymer resin will increase, and there is a risk that the relative density to the theoretical density will decrease to less than 50%.
[0038] Also, disorder reduces the density of the coating and the continuity of the flaky copper powder, thereby decreasing the conductivity of the copper-based composite film.
[0039] The copper powder contained in the copper-based composite film of the present invention is in the form of flakes.
[0040] If the copper powder is not in a flake shape, the X-ray diffraction profile of the copper-based composite film will show an isotropic crystal structure, and the integrated intensity ratio of the copper crystal lattice plane (220) to the (111) in X-ray diffraction may be less than 1 (Figure 4).
[0041] The integrated intensity ratio of the (220) to the (111) crystal lattice plane of copper measured by X-ray diffraction for the spherical shape produced by atomization (Fig. 4(b)) and the irregular dendritic shape produced by electrolysis (Fig. 4(c)) was 4.8 for the flake copper powder (Fig. 4(a)). For,the spherical shape, the value is 0.1 (Fig. 4(b)),and for the dendritic shape, the value is 0.02 (Fig. 4(c)).
[0042] The crystallite size of the copper crystal lattice plane (111) of the flaky copper powder of the present invention, as determined by X-ray diffraction, is preferably 35 nm or less.
[0043] If the size exceeds 35 nm, the flaky copper powder in the copper-based composite film will be difficult to autonomously disperse uniformly and arrange in layers, so there is a risk that the integrated intensity ratio will not be 1 or more.
[0044] The flaky copper powder in the present invention preferably has a 50% diameter / BET diameter ratio of 10 or more.
[0045] If it is less than 10, the flaky copper powder in the copper-based composite film will have difficulty being autonomously dispersed uniformly and arranged in layers, so that there is a risk that the integrated intensity ratio will not be 1 or more.
[0046] Furthermore, copper powder in the form of flakes, spheres, lumps or dendrites with a molecular weight of less than 10 is unlikely to disperse uniformly when kneaded with a polymer resin, and may not form a dense copper-based composite film.
[0047] If the value exceeds 100, the cumulative amount of energy input during flake processing will increase, and the processing time will become longer.
[0048] In addition, the specific surface area of flake copper powder is 4m 2 / g, which may result in poor productivity.
[0049] An increase in the specific surface area leads to an increase in the amount of oxidation on the copper powder surface, which may make it difficult to produce a copper-based composite film that exhibits good electrical conductivity by heat treatment in a nitrogen gas or argon gas atmosphere.
[0050] Therefore, the 50% diameter / BET diameter is preferably 10-100.
[0051] The BET diameter can be calculated using (Equation 3).
[0052] (Formula 3) BET diameter = 6 / (BET specific surface area x true density of copper)
[0053] When the ratio of the 50% diameter measured by laser diffraction to the BET diameter calculated from (Equation 3) (50% diameter / BET diameter) was calculated, it was found that this ratio increases as the powder shape changes from spherical to irregular to flaky, and this ratio was taken as an index value indicating the degree of flaky shape (hereinafter sometimes referred to as the "index value").
[0054] In the flaky copper powder of the present invention, the frequency of particles having a particle size of 51.19 μm or more is preferably 5% or less.
[0055] If it exceeds 5%, the fluidity of the paste decreases when printing to form a coating film, and the paste does not easily come off the printing plate, which may result in a non-uniform cross-sectional shape of the coating film after printing or a reduced surface smoothness, resulting in poor transferability.
[0056] The copper content of the flaky copper powder in the present invention is preferably 93% by weight or more, and more preferably 97% by weight or more.
[0057] When the content is 93% by weight or more, the total amount of components derived from processing agents such as oils and fats used in producing the flaky copper powder, the oxygen content, and the unavoidable components present in the flaky copper powder will be less than 7% by weight at most.
[0058] If the copper content of the flaky copper powder is less than 93% by weight, the resistivity of the copper-based composite film produced by heat treatment in a nitrogen gas atmosphere or an argon gas atmosphere may become high, making it difficult to exhibit good conductivity.
[0059] The content of the flaky copper powder in the copper-based composite film of the present invention is 70% by weight to 95% by weight.
[0060] If the content of the flaky copper powder is less than 70% by weight, it is difficult to achieve an integrated intensity ratio of 1 or more, and the conductivity may decrease.
[0061] This is presumably because, if the content is less than 70% by weight, X-ray diffraction reveals flake copper powder with lattice planes oriented randomly in all directions, so that the X-ray diffraction profile shows an isotropic crystal structure, making it difficult for the flake copper powder contained in the copper-based composite film to autonomously disperse and form a uniform layered arrangement during the lamination process (Figure 1).
[0062] Furthermore, if the content of the flaky copper powder in the copper-based composite film exceeds 95% by weight, it becomes difficult to form a paste, and a large amount of solvent must be mixed.
[0063] Mixing a large amount of solvent reduces the fluidity of the paste, and therefore there is a risk that the shape and thickness of the coating will not be uniform when the paste is applied to a substrate by printing such as screen printing to form a coating.
[0064] Furthermore, the strength of the coating film is weakened, so that it may easily lose its shape due to external forces or its own weight, the adhesion between the coating film and the base layer may be weakened, and the coating film may easily peel off and fall off.
[0065] The copper-based composite film of the present invention can be produced by subjecting a coating film made of a paste containing flaky copper powder, a polymer resin, and a solvent to a heat treatment at a low temperature.
[0066] As the polymer resin, polyvinyl butyral (PVB) and polymer methyl methacrylate (PMMA) are suitable because the copper-based composite film is less likely to crack or blister during the heat treatment process.
[0067] The weight changes of PVB and PMMA measured by thermogravimetry are shown in Figure 5. The results are for PVB in a mixed gas atmosphere of argon gas and argon-3% hydrogen (a) and in air (b), and for PMMA in a mixed gas atmosphere of argon gas and argon-3% hydrogen (c) and in air (d).
[0068] As shown in Figures 5(a) and (c), the weight loss profiles of each polymer resin in an argon gas and argon-3% hydrogen mixed gas atmosphere from room temperature to 500°C are almost the same, with the weight loss up to 300°C being less than 3 wt% for PVB and less than 1 wt% for PMMA.
[0069] Furthermore, as shown in Figures 5(b) and (d), the weight loss of PVB from room temperature to 200°C is less than 0.5% by weight, and the weight loss when held at 200°C for 30 minutes is less than 3.5% by weight.
[0070] In the case of PMMA, the weight loss from room temperature to 200°C is 0.5% by weight or less, and the weight loss when held at 200°C for 30 minutes is 1.0% by weight or less.
[0071] From FIG. 5, it can be seen that although trace amounts of PVB and PMMA disappear upon heat treatment, most remain.
[0072] The solvent in the present invention is preferably butyl carbitol acetate or butyl carbitol, but is not limited thereto.
[0073] Figure 6 shows the changes in X-ray diffraction patterns of the undried coating film immediately after formation of the coating film by printing (Figure 6(a)), the dried coating film after heat treatment at 150°C (Figure 6(b)), and the copper-based composite film after heat treatment at 200°C (Figure 6(c)).
[0074] From Figure 6(a), it can be seen that the integrated intensity ratio is less than 1 immediately after printing, and the flake-shaped copper powder in the coating film is not autonomously dispersed and arranged in uniform layers during the layering process, but is dispersed disorderly.
[0075] As shown in Figure 6(b), when dried at 150 °C in air, the integrated intensity ratio of the copper crystal lattice plane (220) to the copper crystal lattice plane (111) measured by X-ray diffraction becomes greater than 1, and as the solvent contained in the coating evaporates and separates, the volume of the coating shrinks and the flaky copper powder contained in the coating autonomously disperses uniformly and arranges itself in layers, stacking and solidifying.
[0076] FIG. 6(c) shows that the integrated intensity ratio is 1 or more when heat-treated at 200° C. in a nitrogen atmosphere.
[0077] The resistivity of the copper-based composite film of the present invention is preferably 50 μΩ·cm or less.
[0078] If the resistivity exceeds 50 μΩ·cm, heat loss during electrical current flow increases, making it difficult to use the material in electrical conduction components such as electrodes and circuits.
[0079] Furthermore, if the resistivity is large, the thermal conductivity decreases, making it difficult to use the material in the thermal conduction field, such as a heat dissipation sheet.
[0080] A method for producing the copper-based composite film of the present invention will be exemplified.
[0081] A polymer resin and a solvent are kneaded under heating to produce a varnish, and then flaky copper powder is kneaded to produce a paste.
[0082] For the kneading, a mortar mixer, a three-roll mill, a planetary mixer, or the like may be used.
[0083] In order to optimize the printing suitability such as the fluidity of the paste in various printing methods, the solvent used in the varnish may be added as appropriate.
[0084] The method for forming the coating film may be selected from known printing methods depending on the film thickness, film pattern, and the like.
[0085] Examples of printing methods include bar coater and screen printing.
[0086] A coating film is formed by printing on an electrically insulating substrate such as a heat-resistant resin film such as polyimide whose properties are not impaired even when heated, a ceramic substrate such as alumina, or glass.
[0087] The film thickness is preferably 1 μm to 50 μm.
[0088] This is because it is difficult to achieve a film thickness of less than 1 μm.
[0089] Although it is possible to make the film thicker than 50 μm, commercially available copper sheets of the same thickness have resistivities close to those of intrinsic copper, so there is no practical point in producing a copper-based composite film.
[0090] The formed coating film is baked by heat treatment at a temperature of 200° C. to 300° C. in a nitrogen gas atmosphere or an argon gas atmosphere to produce a copper-based composite film.
[0091] Since a nitrogen gas atmosphere or an argon gas atmosphere is a non-oxidizing and non-reducing atmosphere, it is presumed that the flaky copper powder contained in the coating is not affected by oxidation, and during the heat treatment process, a small amount of organic components derived from the flaky copper powder and polymer resin decompose, and the hydrogen and carbon monoxide produced during the decomposition become electron donors, reducing the flaky copper powder. In addition, the powder particles fuse together through the ends of the flaky copper powder due to the diffusion of atoms in the metal crystals at the ends, and the flaky copper powder becomes continuous in the copper-based composite film.
[0092] The heat treatment is preferably carried out in the temperature range of 200°C to 300°C, and more preferably in the temperature range of 250°C to 300°C.
[0093] If the heat treatment is performed at a temperature below 200°C in a nitrogen gas or argon gas atmosphere, the ends of the flake copper powder particles will not fuse sufficiently, resulting in insufficient continuity of the flake copper powder in the copper-based composite film, and there is a risk of increased resistivity.
[0094] Furthermore, if the heat treatment is performed at a temperature exceeding 300°C, the amount of the polymer resin in the coating film that is decomposed and lost will increase, making it easier for the coating film to peel off from the substrate, and there is a risk that the robustness of the copper-based composite film will be difficult to maintain.
[0095] The copper-based composite film of the present invention may be heat-treated by the following method.
[0096] After forming a coating film of the desired thickness by printing, the coating film is heated in an air atmosphere at a temperature range of 150°C to 200°C (heat treatment 1), and then heated in an atmosphere of a mixed gas of nitrogen gas and hydrogen gas or an atmosphere of a mixed gas of argon gas and hydrogen gas at a temperature range of 200°C to 300°C (heat treatment 2), thereby producing the copper-based composite film of the present invention.
[0097] When heated to 150°C in an air atmosphere, the volume of the coating shrinks and the flake-shaped copper powder particles come into contact with each other (heat treatment 1).
[0098] Copper is oxidized when heated to temperatures between 150℃ and 200℃, but the oxidation of the flake copper powder in the coating is suppressed by the polymer resin.
[0099] Heat treatment (heat treatment 2) is performed in a mixed gas atmosphere of nitrogen gas and hydrogen gas or a mixed gas atmosphere of argon gas and hydrogen gas.
[0100] Since hydrogen has reducing properties, the flaky copper powder contained in the copper-based composite film reduces the surface oxidized portions from the time of powdering and the oxidized portions during the heat treatment 1.
[0101] It is also believed that fusion between the ends of the flaky copper powder particles progresses, and the flaky copper powder contained in the coating film becomes continuous, forming the copper-based composite film of the present invention.
[0102] The volumetric flow ratio of nitrogen or argon to hydrogen in the mixed gas is preferably 90:10 to 10:90 (volume %).
[0103] The heat treatment 2 is preferably carried out in the temperature range of 200°C to 300°C, more preferably in the temperature range of 200°C to 250°C.
[0104] In heat treatment 2, if the heat treatment is performed at a temperature below 200°C, the ends of the flaky copper powder particles will not fuse sufficiently, making it difficult for the flaky copper powder in the copper-based composite film to become continuous, which may result in an increase in resistivity.
[0105] If the temperature exceeds 300°C, the weight loss of the polymer resin will progress rapidly, and the decomposition and loss of the polymer resin contained in the coating will become significant. This will lead to peeling between the substrate and the copper-based composite film and deterioration of the copper-based composite film, which may result in a loss of robustness of the copper-based composite film (Figures 6(a) and (c)).
[0106] By performing heat treatment 1 and heat treatment 2 at least once, a copper-based composite film having an integrated intensity ratio of 1 or more is obtained.
[0107] When the heat treatment 1 and the heat treatment 2 are repeated two or more times, the relative density of the copper-based composite film with respect to the theoretical density becomes larger than when the heat treatment is repeated once, the film becomes more dense, and the resistivity becomes smaller.
[0108] During the heat treatment process, the polymer resin gradually disappears, but even after repeating the process three times, most of the polymer resin remains, suppressing the deterioration of the polymer resin and allowing the copper-based composite film to maintain its robustness and exhibit high conductivity. EXAMPLES
[0109] The present invention will be described with reference to examples and comparative examples, but the present invention is not limited to these.
[0110] (Crystallite size) The crystallite size of the flake copper powder was measured using an Ultima IV (Rigaku Corporation) with Kα radiation of a copper target in the measurement range 2θ = 20° to 100°, and calculated from the integral width of the X-ray diffraction peak in the copper crystal lattice plane (111) using Scherrer's formula (Equation 4).
[0111] (Formula 4) Scherrer's formula: D=Kλ / βcosθ D: Crystallite size in the direction perpendicular to the (111) crystal lattice plane λ: wavelength of the target X-ray (Cukα) β: Broadening of diffraction lines due to crystallite size [rad] θ: Diffraction angle K: Scherrer constant (half-width β 1 / 2 If we use 0.9)
[0112] (BET diameter) The specific surface area of the flaky copper powder was measured using a fully automatic BET specific surface area measuring device, Macsorb HM-1208 (manufactured by Mountec Co., Ltd.).
[0113] The BET diameter was calculated from the specific surface area of the flaky copper powder measured by the BET method using the above-mentioned (Equation 3).
[0114] (50% diameter) The 50% diameter of the copper powder was measured using a laser diffraction particle size distribution measuring device SALD-2300 (manufactured by Shimadzu Corporation).
[0115] The 50% diameter / BET diameter was calculated and used as an index value of the degree of flake shape.
[0116] (frequency) The frequency (%) of flaky copper powder particles having a particle size of 51.19 μm or more was measured using a laser diffraction particle size distribution measuring device SALD-2300 (manufactured by Shimadzu Corporation).
[0117] (copper content) The copper content of the flaky copper powder was calculated using Equation 5.
[0118] (Formula 5) Copper content = 100 - (amount of oil and fat + amount of oxygen + amount of unavoidable components)
[0119] (Oil content) Using an EMIA-920V carbon / sulfur analyzer (manufactured by Horiba, Ltd.), flake copper powder was burned together with a combustion improver in an oxygen carrier, and the carbon was converted into carbon dioxide and carbon monoxide, and the sulfur was converted into sulfur dioxide. These were then introduced into a non-dispersive infrared gas analyzer, where a signal change corresponding to the gas concentration occurred due to the infrared absorption characteristics of the gas, and this signal change was processed to determine the gas weight.
[0120] The calculated gas weight was divided by the weight of the sample that had been weighed in advance to determine the carbon amount and sulfur amount.
[0121] The amount of oil and fat was calculated from the carbon amount.
[0122] (oxygen content) The oxygen content was measured using an oxygen / nitrogen analyzer ON830 (manufactured by LECO Japan LLC) by placing flake copper powder in a graphite crucible and melting it in a He atmosphere. The oxygen in the powder was reduced by the carbon in the graphite crucible and extracted as carbon monoxide, and the gas was converted to gas weight using an infrared detector.
[0123] The amount of nitrogen was determined by absorbing and separating the carbon dioxide and moisture produced by heating and melting, and converting the remaining nitrogen into gas weight using a thermal conductivity detector.
[0124] The calculated gas weight was divided by the weighed sample weight to determine the amount of oxygen and the amount of nitrogen.
[0125] (Amount of inevitable ingredients) The amounts of other components in the unavoidable component amounts were measured using a fluorescent X-ray analyzer ZSX PrimusV (manufactured by Rigaku Corporation). The amount of unavoidable components was determined as the total amount of sulfur, nitrogen, and components measured by a fluorescent X-ray analyzer.
[0126] The theoretical density of the copper-based composite film was calculated by the above (Equation 1).
[0127] The true density of copper is 8.94g / cm 3 was used.
[0128] The true density of polymer resin is 1.1g / cm 3 It was calculated as follows.
[0129] (Relative Density) The density of the copper-based composite film was calculated by (Equation 6).
[0130] (Formula 6) Density of copper-based composite film = weight of copper-based composite film / volume of copper-based composite film
[0131] The relative density of the copper-based composite film was calculated by the above-mentioned (Equation 2).
[0132] (integrated intensity ratio) The integrated intensity ratio of the (220) crystal lattice plane of copper to the (111) crystal lattice plane of copper by X-ray diffraction of the copper-based composite film was measured using an Ultima IV (Rigaku Corporation) with Kα radiation of a copper target in the measurement range 2θ = 20° to 100°, and the average count rate was measured with a scaler while changing the angular position of the counter tube, and the integrated intensity ratio of the (111) and (220) crystal lattice planes of copper was calculated.
[0133] (Film thickness) The thickness (t) of the copper-based composite film was measured using a surface profiler DEKTAK3 (manufactured by ULVAC, Inc.).
[0134] (resistivity) The resistivity of the copper-based composite film was calculated by (Equation 7).
[0135] (Formula 7) Resistivity=R×t×b / L
[0136] The resistance value (R) of the copper-based composite film was measured by the four-terminal method using a Milliohm Hitester 3540 (manufactured by Hioki E.E. Corporation).
[0137] The length (L) of the copper-based composite film was measured using a C-type JIS Class 1 ruler (manufactured by Shinwa).
[0138] The film width (b) of the copper-based composite film was measured using a surface profiler DEKTAK3 (manufactured by ULVAC, Inc.).
[0139] Example 1 Flake-shaped copper powder was used as the raw material. X-ray diffraction revealed that the crystallite size of the copper crystal lattice plane (111) was 29 nm. The specific surface area of flake copper powder is 4.38 m 2 / g and the 50% diameter value was 7.133 μm. The 50% diameter / BET diameter (index value) was 46.55. The frequency of particle sizes of 51.19 μm or more was 0.003%, and the copper content was 93.4% by weight.
[0140] Polyvinyl butyral (PVB) resin BL-S (manufactured by Sekisui Chemical Co., Ltd.) was added to butyl carbitol acetate (manufactured by Kanto Chemical Co., Ltd.) to give a varnish at a concentration of 30% by weight.
[0141] The varnish was kneaded with a planetary mixer ARE-310 (Thinky Corporation) so that the flaky copper powder constituted 90% by weight of the solid content, to prepare a paste.
[0142] The paste was applied onto MICRO SLIDE GLASS S-7213 (manufactured by Matsunami Glass Industry Co., Ltd.) by attaching a tape about 50 μm thick to a width of 5 mm and applying it with a squeegee using a flat thin plate to ensure a uniform film thickness.
[0143] The mixture was heated to a temperature of 300° C. in an atmospheric tube furnace KTF045N-AS (manufactured by Koyo Thermo Systems Co., Ltd.) while maintaining a nitrogen gas atmosphere, and held for 30 minutes to obtain a copper-based composite film.
[0144] The integrated intensity ratio of the copper-based composite film of Example 1 was 4.8.
[0145] The X-ray diffraction profile of the copper-based composite film of Example 1 is shown in FIG. 2(a).
[0146] From FIG. 2(a), it can be seen that the integrated intensity of the (220) copper crystal lattice plane is greater than that of the (111) plane.
[0147] The relative density was 82.9% and the resistivity was 19.9 μΩ·cm.
[0148] Example 2 A copper-based composite film was obtained in the same manner as in Example 1, except that the amount of flaky copper powder was 80% by weight.
[0149] Example 3 A coating was formed in the same manner as in Example 1, except that the amount of flaky copper powder was 70% by weight.
[0150] The sample was heated at 200° C. on a hot plate NINOS, ND-1 (manufactured by AS ONE Corporation) in an air atmosphere (heat treatment 1).
[0151] In an atmospheric tube furnace KTF045N-AS (manufactured by Koyo Thermo Systems Co., Ltd.), the sample was heated to a temperature of 200°C while maintaining an atmosphere of a mixed gas of nitrogen:hydrogen = 80:20 (volume %) and held for 30 minutes (heat treatment 2) to obtain a copper-based composite film.
[0152] Example 4 Flake-shaped copper powder was used as the raw material. X-ray diffraction revealed that the crystallite size of the copper crystal lattice plane (111) was 30.1 nm. The specific surface area of flake copper powder is 2.75m 2 / g and the 50% diameter value was 12.505 μm. The 50% diameter / BET diameter (index value) was 51.24. The frequency of particles with a particle size of 51.19 μm or more was 0.267%, and the copper content was 97.1 wt%.
[0153] A coating film was formed in the same manner as in Example 1, except that the type of flaky copper powder was different.
[0154] In an atmospheric tube furnace KTF045N-AS (manufactured by Koyo Thermo Systems Co., Ltd.), the mixture was heated to a temperature of 250° C. while maintaining a nitrogen gas atmosphere, and held for 30 minutes to obtain a copper-based composite film.
[0155] Example 5 Flake-shaped copper powder was used as the raw material. X-ray diffraction revealed that the crystallite size of the copper crystal lattice plane (111) was 34.2 nm. The specific surface area of flake copper powder is 2.44m 2 / g and the 50% diameter value was 14.142 μm. The 50% diameter / BET diameter (index value) was 51.41. The frequency of particles with a particle size of 51.19 μm or more was 0.243%, and the copper content was 96.1 wt%.
[0156] A coating film was formed in the same manner as in Example 1, except that the type of flaky copper powder was different.
[0157] The material was heated to a temperature of 250° C. while maintaining a nitrogen gas atmosphere in an atmospheric tube furnace KTF045N-AS (manufactured by Koyo Thermo Systems Co., Ltd.) and held for 30 minutes to obtain a copper-based composite film.
[0158] Example 6 The same flaky copper powder as in Example 1 was used. Methyl methacrylate polymer (PMMA) (manufactured by Wako Pure Chemical Industries, Ltd.) was added to butyl carbitol acetate (manufactured by Kanto Chemical Co., Ltd.) to give a concentration of 30% by weight to prepare a varnish.
[0159] The flaky copper powder was mixed into the varnish so that the content was 90% by weight to prepare a paste, and a coating film was formed in the same manner as in Example 1.
[0160] The mixture was heated to a temperature of 250° C. while maintaining a nitrogen gas atmosphere in an atmospheric tube furnace KTF045N-AS (manufactured by Koyo Thermo Systems Co., Ltd.), and held for 30 minutes to obtain a copper-based composite film.
[0161] Example 7 A copper-based composite film was obtained in the same manner as in Example 1, except that the heat treatment temperature was 275°C.
[0162] Example 8 A copper-based composite film was obtained in the same manner as in Example 1, except that the heat treatment was performed in an argon gas atmosphere at a temperature of 250°C.
[0163] Example 9 A coating film was formed in the same manner as in Example 1.
[0164] The sample was heated at 200° C. on a hot plate NINOS, ND-1 (manufactured by AS ONE Corporation) in an air atmosphere (heat treatment 1).
[0165] In an atmospheric tube furnace KTF045N-AS (manufactured by Koyo Thermo Systems Co., Ltd.), the sample was heated to 200°C while maintaining a mixed gas atmosphere of nitrogen:hydrogen = 80:20 (volume %) and held for 30 minutes (heat treatment 2) to obtain a copper-based composite film.
[0166] Example 10 A copper-based composite film was obtained in the same manner as in Example 9, except that the temperature of the heat treatment 2 was 225°C.
[0167] Example 11 A copper-based composite film was obtained in the same manner as in Example 9, except that the temperature of the heat treatment 2 was 250°C.
[0168] Example 12 A copper-based composite film was obtained in the same manner as in Example 9, except that the temperature of the heat treatment 2 was 300°C.
[0169] Example 13 A copper-based composite film was obtained in the same manner as in Example 9, except that the atmosphere in the heat treatment 2 was a mixed gas of nitrogen:hydrogen=90:10 (volume %).
[0170] Example 14 A copper-based composite film was obtained in the same manner as in Example 9, except that the atmosphere in the heat treatment 2 was a mixed gas of nitrogen:hydrogen=50:50 (volume %).
[0171] Example 15 A copper-based composite film was obtained in the same manner as in Example 9, except that the atmosphere in the heat treatment 2 was a mixed gas of nitrogen:hydrogen=20:80 (volume %).
[0172] Example 16 A copper-based composite film was obtained in the same manner as in Example 9, except that the atmosphere for the heat treatment was a mixed gas of argon gas:hydrogen=80:20 (volume %).
[0173] Example 17 A coating film was formed in the same manner as in Example 1.
[0174] After heat treatment (heat treatment 1) at 200°C on a hot plate NINOS ND-1 (manufactured by AS ONE Corporation) in an air atmosphere, the film was heated to 200°C in an atmospheric tube furnace KTF045N-AS (manufactured by Koyo Thermo Systems Co., Ltd.) while maintaining an atmosphere of a mixed gas of nitrogen:hydrogen = 80:20 (volume %) and held for 30 minutes (heat treatment 2). This heat treatment was repeated a total of two times to obtain a copper-based composite film.
[0175] A scanning electron microscope image showing the cross-sectional structure of the copper-based composite film of Example 17 is shown in FIG. It can be seen that the flake copper powder is autonomously arranged and laminated into uniform layers.
[0176] Example 18 A coating film was formed in the same manner as in Example 1.
[0177] After heat treatment (heat treatment 1) at 200°C on a hot plate NINOS ND-1 (manufactured by AS ONE Corporation) in an air atmosphere, the film was heated to 200°C in an atmospheric tube furnace KTF045N-AS (manufactured by Koyo Thermo Systems Co., Ltd.) while maintaining a mixed gas atmosphere of nitrogen:hydrogen = 80:20 (volume %) and held for 30 minutes. This heat treatment was repeated three times in total to obtain a copper-based composite film.
[0178] Comparative Example 1 Flake-shaped copper powder was used as the raw material. X-ray diffraction revealed that the crystallite size of the copper crystal lattice plane (111) was 39.7 nm. The specific surface area of flake copper powder is 3.00m 2 / g and the 50% diameter value was 3.764 μm. The 50% diameter / BET diameter (index value) was 16.83. The frequency of particles with a particle size of 51.19 μm or more was 0.000%, and the copper content was 95.5% by weight.
[0179] A copper-based composite film was obtained in the same manner as in Example 1, except that the flaky copper powder was different and the heat treatment temperature was 250°C.
[0180] The integrated intensity ratio of the (220) crystal lattice plane of copper to the (111) crystal lattice plane of copper in the copper-based composite film by X-ray diffraction was 0.7.
[0181] The X-ray diffraction profile of the copper-based composite film of Comparative Example 1 is shown in FIG. 2(b). From FIG. 2(b), it can be seen that the integrated intensity of the (220) copper crystal lattice plane is smaller than that of the (111) plane.
[0182] Comparative Example 2 A copper-based composite film was obtained in the same manner as in Example 1, except that the amount of flaky copper powder was 30 wt % and the heat treatment temperature was 250°C.
[0183] The integrated intensity ratio of the (220) crystal lattice plane of copper to the (111) crystal lattice plane of copper in the copper-based composite film by X-ray diffraction was 0.9.
[0184] Comparative Example 3 A copper-based composite film was obtained in the same manner as in Example 1, except that the amount of flaky copper powder was 50% by weight and the heat treatment temperature was 250°C.
[0185] A scanning electron microscope image showing the cross-sectional structure of the copper-based composite film of Comparative Example 3 is shown in FIG.
[0186] From Figure 3(b), it can be seen that the flake-like copper powder in the copper-based composite film is not stacked in a uniform layered arrangement.
[0187] Comparative Example 4 A copper-based composite film was obtained in the same manner as in Example 3, except that the amount of flaky copper powder was 50% by weight.
[0188] The integrated intensity ratio of the (220) crystal lattice plane of copper to the (111) crystal lattice plane of copper measured by X-ray diffraction of the copper-based composite film of Comparative Example 4 was 2.3, but the resistivity was as high as 1119.0 μΩ·cm.
[0189] Comparative Example 5 A copper-based composite film was obtained in the same manner as in Example 3, except that the amount of flaky copper powder was 30 wt %.
[0190] The integrated intensity ratio of the (220) crystal lattice plane of copper to the (111) crystal lattice plane of copper by X-ray diffraction of the copper-based composite film of Comparative Example 5 was 1.6, but the resistance value was unmeasurable and was in the insulating region.
[0191] Comparative Example 6 Dendritic copper powder was used as the raw material.
[0192] X-ray diffraction revealed that the crystallite size of the copper crystal lattice plane (111) was 77 nm. The specific surface area of copper powder is 0.39m 2 / g and the 50% diameter value was 15.887 μm. The 50% diameter / BET diameter (index value) was 9.23. The frequency of particle sizes of 51.19 μm or more was 1.100%, and the copper content was 99.1 wt%.
[0193] A copper-based composite film was obtained in the same manner as in Example 1, except that the copper powder was dendritic and the heat treatment temperature was 250°C.
[0194] The X-ray diffraction profile of the copper-based composite film of Comparative Example 6 is shown in FIG. From FIG. 4(c), it can be seen that the integrated intensity of the (220) crystal lattice plane of copper is smaller than that of the (111) plane.
[0195] The integrated intensity ratio of the (220) crystal lattice plane of copper to the (111) crystal lattice plane of copper measured by X-ray diffraction was 0.02.
[0196] Comparative Example 7 Spherical copper powder was used as the raw material. X-ray diffraction reveals that the crystallite size of the (111) crystal lattice plane of copper is 58 nm. The specific surface area of the powder is 0.21 m 2 / g and the 50% diameter value was 4.414 μm. The 50% diameter / BET diameter (index value) was 1.38. The frequency of particles with a particle size of 51.19 μm or more was 0.000%, and the copper content was 99.8% by weight.
[0197] A copper-based composite film was obtained in the same manner as in Example 1, except that the copper powder was spherical and the heat treatment temperature was 250°C.
[0198] The X-ray diffraction profile of the copper-based composite film of Comparative Example 7 is shown in FIG. Figure 4(b) shows that the integrated intensity of the (220) crystal lattice plane of copper is smaller than that of the (111) plane.
[0199] The integrated intensity ratio of the (220) crystal lattice plane of copper to the (111) crystal lattice plane of copper measured by X-ray diffraction was 0.1.
[0200] The copper powders used in the examples and comparative examples are shown in Tables 1 and 2. The results are shown in Tables 3 and 4.
[0201] In the atmosphere columns of the heat treatment conditions in Tables 1 and 2, N2 is nitrogen gas, H2 is hydrogen gas, and Ar is argon gas, and the units of values are volume percent. A "-" in the oxidation / reduction cycle number column for heat treatment conditions indicates that the heat treatment was performed without using reducing hydrogen. The integrated intensity ratio of the copper-based composite film is the integrated intensity ratio of the (220) crystal lattice plane of copper to the (111) plane by X-ray diffraction. This indicates that the resistivity of the composite film is not measurable beyond ∞ and is an insulating region.
[0202] [Table 1]
[0203] [Table 2]
[0204] [Table 3]
[0205] [Table 4] [Industrial Applicability]
[0206] The present invention provides a copper-based composite film having high conductivity because the flaky copper powder has a high planar density and is layered in an arrangement that allows the flaky copper powder particles to easily come into contact with each other. Moreover, the copper-based composite film can be produced by low-temperature heat treatment, making it suitable for use in parts in the electrical conductivity and thermal conductivity fields. Therefore, the present invention has high industrial applicability.
Claims
1. A copper-based composite film, comprising: A copper-based composite film having a flake copper powder content of 70% by weight or more and 95% by weight or less, a relative density of 50% or more with respect to theoretical density, and an integrated intensity ratio of the copper crystal lattice plane (220) to the copper crystal lattice plane (111) by X-ray diffraction of 1 or more.
2. 2. The copper-based composite film according to claim 1, which has a resistivity of 50 μΩ·cm or less.
3. 3. The flaky copper powder of claim 1 or 2, wherein the crystallite size of the copper crystal lattice plane (111) determined by X-ray diffraction is 35 nm or less, the "50% cumulative particle size" / "particle size calculated from the BET specific surface area of the flaky copper powder" is 10 or more, the frequency of particle sizes of 51.19 μm or more is 5% or less, and the copper content is 93% by weight or more.
4. 3. The method for producing a copper-based composite film according to claim 1, wherein the film is produced by applying a paste containing flaky copper powder, a polymeric resin and a solvent, followed by a heat treatment.
5. 5. The method for producing a copper-based composite film according to claim 4, wherein the polymer resin is polyvinyl butyral and / or methyl methacrylate polymer, and the solvent is butyl carbitol acetate and / or butyl carbitol.
6. 5. The method for producing a copper-based composite film according to claim 4, wherein the heat treatment is performed in a nitrogen gas atmosphere or an argon gas atmosphere at a temperature range of 200° C. or more and 300° C. or less.
7. 5. The method for producing a copper-based composite film according to claim 4, wherein the heat treatment is a heat treatment that repeats at least once a heat treatment (heat treatment 1) in an air atmosphere at a temperature range of 150° C. or more and 200° C. or less, and a heat treatment (heat treatment 2) in an atmosphere of a mixed gas of nitrogen gas and hydrogen gas or an atmosphere of a mixed gas of argon gas and hydrogen gas at a temperature range of 200° C. or more and 300° C. or less.
Citation Information
Patent Citations
Conductive film
JP2014222619A